Psychocardiology, discipline is essential in these times - Teresa Rodríguez Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
The paper addresses the need to consider Psychocardiology indispensable in modern times, taking into account the continuous increase of cardiovascular disease, implying the existence of genetic markers, as well as psychological and social factors. Emphasis is on considering the psychological intervention on prevention and rehabilitation for these conditions, the psychological aspects associated with invasive procedures in patients with coronary artery disease, the changes arising from acute illness and the critical condition of the patient also changes cognitive order result of changes in the microcirculation and cardiac ischemia. It emphasizes the importance of giving the study and psychological interventions in heart disease and a gender focus to include the study of the family as the cradle of learning styles of life, social support agent, as well as subjects that involved directly in the complex network of heart disease by genetic markers. It appeals to the need to sensitize medical professionals and doctors in the multifactorial approach of these diseases, as the only way to reduce morbidity and mortality from this cause and raise the quality of life of coronary patients.